2022
DOI: 10.1155/2022/8161684
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PEEK Particles on Physiomechanical Behavior of Carbon/Epoxy Composite

Abstract: The inherently brittle nature and the susceptibility to impact damage hinder the use of carbon/epoxy composite in some areas. In this study, poly ether ether ketone (PEEK) microparticles were incorporated to increase the resistance to delamination and interlaminar fracture toughness. A hand lay-up technique followed by compression molding was used to fabricate composite. The influence of PEEK particles was evaluated by tensile, flexural, short beam shear (SBS), compression, and Charpy impact test. The Barcol h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Therefore, a combination of metals and composites is used in aerospace structures. Due to the differences between the two, the joining of these components has been a serious problem [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a combination of metals and composites is used in aerospace structures. Due to the differences between the two, the joining of these components has been a serious problem [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is either hybridized with some other reinforcement material [20] or a third component is usually added to achieve the required properties. This third-phase material can be either chopped fiber, filler, or particulate [21][22][23]. The synergistic effects of all components in a composite help to achieve mechanical properties that cannot be possible by individual contributing material [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, airplane structures such as fuselage, fan blades, and wings are made of carbon-fiber-reinforced composites and metal alloys. [1,2] Park et al [3] reported that due to the different natures of the two materials, joining composite components with metal alloys has been a serious problem. [4][5][6] Beiss et al [7] and Rhee et al [8] reported that the most common method of joining composite parts is adhesive bonding.…”
Section: Introductionmentioning
confidence: 99%